The use of flashcards to improve the mastery of Arabic vocabulary in Madrasah Ibtidaiyah Perwanida Blitar - Sumiati, Sumiati (Maliki Interdisciplinary Journal, 2024)
This research aims to examine the effectiveness of using flashcards in improving Arabic vocabulary mastery at Madrasah Ibtidaiyah Perwanida, Blitar City. The research method used was experimental research with a pre-test and post-test design in two classes of fifth grade students for the 2023/2024 academic year. The experimental group was given treatment using flashcard media, while the control group used conventional methods. The results of the study showed that there was a significant increase in mastery of Arabic vocabulary in the group that used flashcard media compared to the group that used conventional methods. Data analysis using the t-test showed a calculated t-value of 4.32 which was greater than the t-table of 2.00 at a significance level of 0.05, indicating that the use of flashcard media was effective in increasing mastery of Arabic vocabulary. The conclusion of this research is that the use of flashcards can significantly increase students’ mastery of Arabic vocabulary at Madrasah Ibtidaiyah Perwanida. This media can be an effective alternative in learning Arabic and is recommended to be applied more widely in other madrasas. The implementation of flashcard media not only increases students’ learning motivation but also provides a more enjoyable and interactive learning experience.